2000
DOI: 10.1103/physrevb.61.2513
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagrams and Fermi surface properties ofCePb3

Abstract: We illustrated the phase diagrams and measured the de Haas-van Alphen effect of CePb 3 , which is a heavy fermion compound with an antiferromagnetic transition at 1.1 K. CePb 3 has three phases: antiferromagnetic, spin-flop, and paramagnetic. Three fundamental oscillations denoted by ␣, ␤, and ␥ were observed in the paramagnetic state. Two of them, the ␣ and ␥ branches, are closed and almost spherical. For the ␣ branch, the natural explanation is provided by the results of band calculation. The heaviest cyclot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The (Pb, Ce) system was chosen for two main reasons. First, the CePb 3 bulk material is a heavyfermion type-I antiferromagnet with a Néel transition temperature T N of 1.1 K. 20,21 Magnetic field (15 T) is known to induce superconductivity in the material that stimulates considerable theoretical and practical interest. 22 The intra-atomic spin-orbit coupling (SOC) of the 4f electrons of rare earth elements is large, and thus effective moments of the total angular momentum J > 1/2 encompass both spins and higher multipolar moments.…”
Section: Introductionmentioning
confidence: 99%
“…The (Pb, Ce) system was chosen for two main reasons. First, the CePb 3 bulk material is a heavyfermion type-I antiferromagnet with a Néel transition temperature T N of 1.1 K. 20,21 Magnetic field (15 T) is known to induce superconductivity in the material that stimulates considerable theoretical and practical interest. 22 The intra-atomic spin-orbit coupling (SOC) of the 4f electrons of rare earth elements is large, and thus effective moments of the total angular momentum J > 1/2 encompass both spins and higher multipolar moments.…”
Section: Introductionmentioning
confidence: 99%
“…The suppression of the superconducting transition temperature by impurities was observed. From the temperature dependence of resistivity for LaPb 3 Kletowski et al [5] estimated the Debye temperature θ as 125 K. Ebihara et al [7] have found the phase diagrams of CePb 3 and they observed three phases: antiferromagnetic, spin op, and paramagnetic. The phase diagram and de Haasvan Alphen (dHvA) eect of PrPb 3 under pressure was also studied by Endo et al [9].…”
Section: Introductionmentioning
confidence: 99%